ANALYSIS OF ACCOUNTABILITY AND TRANSPARENCY IN THE MANAGEMENT OF FUNDS FOR EDUCATIONAL INSTITUTIONS OF PUBLIC SENIOR HIGH SCHOOL (SMA) 8 PEKANBARU CITY - Sri Susanti, Roza (Universitas Islam Lamongan, 2024)
This study aims to analyze the accountability and transparency of the management of funds for public high school education institutions in Pekanbaru city. In 2020 SMA Negeri 8 is a public school in Pekanbaru city with the largest number of students, with this number of students SMA Negeri 8 is the recipient of the most School Operational Assistance (BOS) funds compared to other State Senior High Schools in Pekanbaru city. Being the school with the most funding recipients, makes the related school become a target and questioned how the funds are managed. In the management of education funds, accountability and use of funds are adjusted to technical guidelines, some important indicators that must be considered in the management of education funds are accountability and transparency. This research is a case study research with a descriptive approach and the sample studied was 60 people consisting of school principals, school BOS fund treasurers and teachers at SMA Negeri 8 Pekanbaru.